Original height = original width = x mm
1. She made an enlarged copy...
height = 2x
width = 2x
2. She cut off a rectangle...
height = 2x
width =
![\frac{2}{3} *2x= \frac{4}{3}x](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20%2A2x%3D%20%5Cfrac%7B4%7D%7B3%7Dx%20%20%20)
3.She doubled the width...
height = 2x
width =
![2*\frac{4}{3}x = \frac{8}{3}x](https://tex.z-dn.net/?f=2%2A%5Cfrac%7B4%7D%7B3%7Dx%20%3D%20%5Cfrac%7B8%7D%7B3%7Dx%20)
height * width = area
![2x * \frac{8}{3}x=139 \ 968 \\ \\ \frac{16}{3}x^2= 139 \ 968 \\\\ x^2=139 \ 968: \frac{16}{3}=139 \ 968 * \frac{3}{16}= 8 \ 748*3 = 26 \ 244 \\ \\ x= \sqrt{26 \ 244} = 162 \ mm](https://tex.z-dn.net/?f=2x%20%2A%20%5Cfrac%7B8%7D%7B3%7Dx%3D139%20%5C%20968%20%20%5C%5C%20%5C%5C%20%5Cfrac%7B16%7D%7B3%7Dx%5E2%3D%20139%20%5C%20968%20%5C%5C%5C%5C%20x%5E2%3D139%20%5C%20968%3A%20%5Cfrac%7B16%7D%7B3%7D%3D139%20%5C%20968%20%2A%20%5Cfrac%7B3%7D%7B16%7D%3D%20%208%20%5C%20748%2A3%20%3D%2026%20%5C%20244%20%5C%5C%20%20%5C%5C%20x%3D%20%5Csqrt%7B26%20%5C%20244%7D%20%3D%20162%20%5C%20mm%20)
Original height was
162 mm
Answer:
9 and 11
Step-by-step explanation:
First number = x -2
Second number = x
and 2x = 3(x-2) - 5
2x = 3x - 6 - 5
x = 11
first number = 11-2 = 9
Answer:
x+2 is a factor of ![f(x) = 5x^2 + 13x + 6](https://tex.z-dn.net/?f=f%28x%29%20%20%3D%205x%5E2%20%2B%2013x%20%2B%206)
Step-by-step explanation:
To check: If (x+2) is a a factor of the polynomial ![f(x) = 5x^2 + 13x + 6](https://tex.z-dn.net/?f=f%28x%29%20%20%3D%205x%5E2%20%2B%2013x%20%2B%206)
We need to check if x = -2 is the FACTOR of the given polynomial.
⇒ To show: f (-2) = 0
Now
![f(-2) = 5(-2)^2 + 13(-2) + 6\\=5(4) -26 + 6\\= 20 + 6 - 26\\= 26 - 26 = 0\\\implies f(-2) = 0](https://tex.z-dn.net/?f=f%28-2%29%20%20%3D%205%28-2%29%5E2%20%2B%2013%28-2%29%20%2B%206%5C%5C%3D5%284%29%20-26%20%2B%206%5C%5C%3D%2020%20%2B%206%20-%2026%5C%5C%3D%2026%20-%2026%20%20%3D%200%5C%5C%5Cimplies%20f%28-2%29%20%3D%200)
Since, f(-2) = 0
⇒ -2 is the ROOT of the Polynomial f(x).
⇒(x +2) is the factor of the given polynomial.
Hence, x+2 is a factor of ![f(x) = 5x^2 + 13x + 6](https://tex.z-dn.net/?f=f%28x%29%20%20%3D%205x%5E2%20%2B%2013x%20%2B%206)
Answer:
-4 1/12.
Step-by-step explanation:
-9/2 + 5 /12
The Lowest Common denominator is 12 so we have:
-54/12 + 5/12
= -49/12
= -4 1/12.